2008
DOI: 10.1080/10635150802032990
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Reliability of Genetic Methods of Species Identification via Simulation

Abstract: Although genetic methods of species identification, especially DNA barcoding, are strongly debated, tests of these methods have been restricted to a few empirical cases for pragmatic reasons. Here we use simulation to test the performance of methods based on sequence comparison (BLAST and genetic distance) and tree topology over a wide range of evolutionary scenarios. Sequences were simulated on a range of gene trees spanning almost three orders of magnitude in tree depth and in coalescent depth; that is, deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
306
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(315 citation statements)
references
References 44 publications
4
306
2
3
Order By: Relevance
“…There is no single optimal method to determine the resolving power of DNA barcodes for all taxa (Austerlitz et al., 2009; Casiraghi et al., 2010; Collins & Cruickshank, 2013; Meyer & Paulay, 2005; Moritz & Cicero, 2004; Ross et al., 2008). Different approaches exist for matching an unknown query sequence with sequences in a reference database or library and tend to be based on ad hoc criteria which may include the frequency of the highest hits, percentage sequence similarity, bootstrapping, BLAST scores or tree‐based clustering assessment (Kress et al., 2009; Wilson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no single optimal method to determine the resolving power of DNA barcodes for all taxa (Austerlitz et al., 2009; Casiraghi et al., 2010; Collins & Cruickshank, 2013; Meyer & Paulay, 2005; Moritz & Cicero, 2004; Ross et al., 2008). Different approaches exist for matching an unknown query sequence with sequences in a reference database or library and tend to be based on ad hoc criteria which may include the frequency of the highest hits, percentage sequence similarity, bootstrapping, BLAST scores or tree‐based clustering assessment (Kress et al., 2009; Wilson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NJ trees were used to establish clustering of query sequences into correct genus‐specific groups with strong bootstrap support and were not used to infer phylogeny. Poor resolution in tree topologies with low bootstrap scores and polytomies obtained for rbcL sequences were obtained which may be due to inadequate low genetic distances for most species (Hebert et al., 2003; Hollingsworth et al., 2016; Kress et al., 2009; Ross et al., 2008; Wilson et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such simple queries permit the user to examine and establish whether the expected species are present among the available ITS sequences in the database. Ross et al (2008) and Ovaskainen et al (2010) provide interesting statistics on the performance of BLAST under varying conditions, including incomplete database coverage.…”
Section: Guideline 4 Sequences Can Be Broken In Other Puzzling Waysmentioning
confidence: 99%
“…The correct identification rates of all barcodes in ASB were rapidly decreased comparing to BCM, except rbcL (increased from 34.4% to 43.9%). Singletons are also a source of incorrect identification due to the absence of other conspecific reference sequences in the dataset without matching (Ross et al 2008). Lahaye et al (2008) showed that matK and rbcL barcoding cannot yield a barcode gap in the closely related plant species.…”
Section: Specimens Identification Ability Of Dna Barcodingmentioning
confidence: 99%